An Equivalence Trial Comparing Instructor-Regulated With Directed Self-Regulated Mastery Learning of Advanced Cardiac Life Support Skills. Issue 4 (August 2015) - Devine, Luke A.; Donkers, Jeroen; Brydges, Ryan; Perelman, Vsevolod; Cavalcanti, Rodrigo B.; Issenberg, S. Barry
<x xml:space="preserve">Abstract</x> Introduction Instructor-led simulation-based mastery learning of advanced cardiac life support (ACLS) skills is an effective and focused approach to competency-based education. Directed self-regulated learning (DSRL) may be an effective and less resource–intensive way to teach ACLS skills. Methods Forty first-year internal medicine residents were randomized to either simulation-based DSRL or simulation-based instructor-regulated learning (IRL) of ACLS skills using a mastery learning model. Residents in each intervention completed pretest, posttest, and retention test of their performance in leading an ACLS response to a simulated scenario. Performance tests were assessed using a standardized checklist. Residents in the DSRL intervention were provided assessment instruments, a debriefing guide, and scenario-specific teaching points, and they were permitted to access relevant online resources. Residents in the IRL intervention had access to the same materials; however, the teaching and debriefing were instructor led. Results Skills of both the IRL and DSRL interventions showed significant improvement after the intervention, with an average improvement on the posttest of 21.7%. After controlling for pretest score, there was no difference between intervention arms on the posttest [F(1, 37) = 0.02, P = 0.94] and retention tests [F(1, 17) = 1.43, P = 0.25]. Cost savings were realized in the DSRL intervention after the fourth group (16 residents) had completed each intervention, with an ongoing savings of $80 per resident. Conclusions Using a simulation-based mastery learning model, we observed equivalence in learning of ACLS skills for the DSRL and IRL conditions, whereas DSRL was more cost effective.